Childhood sexual abuse : a reference handbook - Kinnear, Karen L. (Santa Barbara, Calif. : ABC-CLIO, 2007)
"Also includes information on age of consent, age of majority, definition of child, community notification laws, etc."--Source other than the Library of Congress.
Summary of Significant Court Cases in U.S. Courts -- New York v. Ferber, 458 U.S. 747 (1982) -- Osborne v. Ohio, 495 U.S. 103 (1990) -- Idaho v. Wright, 497 U.S. 805 (1990) -- Reno v. American Civil Liberties Union, 521 U.S. 844 (1997) -- Ashcroft v. Free Speech Coalition, 535 U.S. 234 (2002) -- Stogner v. California, 539 U.S. 607 (2003) -- Ashcroft v. American Civil Liberties Union, 542 U.S. 656 (2004) -- Smith et al. v. Doe et al., 538 U.S. 84 (2002) -- United States v. American Library Association, 539 U.S. 194 (2003) -- United States v. Hilton, 363 F.3d 58 (1st Cir. 2004) -- Cummings v. State of Arkansas 353 Ark. 618 (Ark. Sup. Ct. 2003) -- Doe v. Chamberlin (299 F.3d 192 (3rd Cir. 2002) -- References -- 7. Directory of Organizations, Associations, and Agencies.
Includes bibliographical references and index.
Keywords: Child sexual abuse; Child sexual abuse -- Prevention; Sexually abused children; Enfants victimes d'abus sexuels; Child sexual abuse; Child sexual abuse -- Prevention; Sexually abused children